PENERAPAN PERSONAL HYGIENE DI FOOD AND BEVERAGE PRODUCT GRAND JATRA HOTEL PEKANBARU - Wulansari, Rizki Desi; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research aims to determine Applying Personal Hygiene and way of to constraint existing overcoming in Food & Beverage Department Grand Jatra Hotel Pekanbaru.This research was used descriptif qulitatif method to describe the issues. The population in this research was used Sensus technique, and the subject is all employee in Food and Beverage Department. The research was used observation, interview and documentation for gathering the data.Based on the research that has been done, Applying Personal Hygiene in Food and Beverage Department Grand Jatra Pekanbaru Hotel was good enough and according to Standard Operational Procedure that has been made by the company.Keywords: Applying Personal Hygiene, Standard Operational Procedure, Kitchen, Chef, Hotel